Vagus nerve spiking activity associated with locomotion and cortical arousal states in a freely moving rat. (8th December 2018) - Shikano, Yu; Nishimura, Yuya; Okonogi, Toya; Ikegaya, Yuji; Sasaki, Takuya
Abstract: The vagus nerve serves as a central pathway for communication between the central and peripheral organs. Despite traditional knowledge of vagus nerve functions, detailed neurophysiological dynamics of the vagus nerve in naïve behavior remain to be understood. In this study, we developed a new method to record spiking patterns from the cervical vagus nerve while simultaneously monitoring central and peripheral organ bioelectrical signals in a freely moving rat. When the rats transiently elevated locomotor activity, the frequency of vagus nerve spikes was correspondingly increased, and this activity was retained for several seconds after the increase in running speed terminated. Spike patterns of the vagus nerve were not robustly associated with which arms the animals entered on an elevated plus maze. During sniffing behavior, vagus nerve spikes were nearly absent. During stopping, the vagus nerve spike patterns differed considerably depending on external contexts and peripheral activity states associated with cortical arousal levels. Stimulation of the vagus nerve altered rat's running speed and cortical arousal states depending on running speed at the instant of stimulation. These observations are a new step for uncovering the physiological dynamics of the vagus nerve modulating the visceral organs such as cardiovascular, respiratory, and gastrointestinal systems. Abstract : Vagus nerve spikes increased with locomotion and the increased activity was retained for several seconds. During stopping, the vagus nerve spike patterns differed depending on external contexts and peripheral activity states associated with cortical arousal levels. These results are a new step for uncovering the physiological dynamics of the vagus nerve.